Integrating The Traditional Game Gasing: Comparison and Correlation of Responses, Peace-Loving Character, Social Care, and Student Responsibility - Alirmansyah Alirmansyah; Muhammad Dewa Zulkhi; Pebri Azmi Pandya; Aqilla Fadia Haya; Vidia Wulandari (Journal of Innovation in Educational and Cultural Research, 2024)
The era of globalization and the rapid development of technology have made many children prefer online games over traditional games. This makes it difficult for children to socialize with the surrounding environment and have high individual character; one of the traditional games is gasing (spinning top). This research aims to compare students' responses and characters towards the integration of traditional game gasing and to see the relationship between each variable to be studied. The research method uses mixed-method research. This research used a sample of 56 class IIIA and class IIIB students at SDN 55/I Sridadi, and the sampling technique used was total sampling. The data collection instruments used were questionnaires and interviews. Data analysis uses descriptive statistics and inferential statistics. The results of this research are that there is a significant relationship between variables, and it also produces a positive relationship, namely 0.00 0.05. Meanwhile, the results of the t-test comparison of each response variable, peace-loving character, social care character, and responsibility, have a significant comparison, with sig values of 0.000.05 and 0.020.05 and, respectively, dominant variable in the response variable in the good category. There is a need to develop innovative and educational traditional games to maintain their value and sustainability.